AHP-De Borda: a hybrid multicriteria ranking method - Costa, Helder Gomes (Brazilian Journal of Operations & Production Management, 2017)
De Borda voting method was proposed in the period of French revolution to be used in a multiple decision-maker environment. Later, it was adapted to multicriteria ranking problems. The adoption of criteria weights in De Borda modeling is an evolution of the original De Borda method; despite this fact, evolution does not approach how to define the weights, that is: the weights are an input to De Borda. The proposal is to segment the problem into two ones. The first is a weight assignment problem and was approached through AHP modeling. The second problem is a ranking problem, being approached through De Borda method. AHP and De Borda are based in principles from different multicriteria Decision Schools: AHP is classified into the American School; De Borda is recognized as a French method. This paper shows that it is possible to use both methods, in a complementary way. The proposal can assist and support decision makers in the modeling of multicriteria ranking problems by assigning weights to the criteria under a systematized way. This hybrid approach proposes a better way for the structuring of the problem, by linking an approach that natively supports the assignment of weights (AHP) into another devoted to the ordering of objects (De Borda).